1998
DOI: 10.1159/000045167
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Leukocyte Activation during Hemodialysis Detected with a Monoclonal Antibody to Leukocyte Integrin CD11b

Abstract: Platelet activation is commonly monitored with a battery of monoclonal antibodies against different platelet epitopes with controversial results. The transient expression of platelet markers and their role mediating interactions with other cells could easily explain these discrepancies. The present study has evaluated whether the analysis of a leukocyte activation antigen (CD11b) could provide more reliable results than detection of platelet activation markers. Cytometric techniques with specific monoclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
5
13
0
Order By: Relevance
“…In previous studies, we have already evaluated the biocompatibility of dialysis membranes. Results from those studies confirm previous data indicating that different membranes have variable ability to activate platelets and leukocytes assessed by differences in the percentages of heterotypic aggregates formed and by a priming state observed in leukocytes of hemodialysis patients [3, 26]. In contrast, the cellular adhesion process is not dependent on the type of dialysis membrane, as no differences were observed between a cellulosic and a synthetic membrane.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In previous studies, we have already evaluated the biocompatibility of dialysis membranes. Results from those studies confirm previous data indicating that different membranes have variable ability to activate platelets and leukocytes assessed by differences in the percentages of heterotypic aggregates formed and by a priming state observed in leukocytes of hemodialysis patients [3, 26]. In contrast, the cellular adhesion process is not dependent on the type of dialysis membrane, as no differences were observed between a cellulosic and a synthetic membrane.…”
Section: Discussionsupporting
confidence: 86%
“…Leukocyte activation and heterotypic aggregation to recruit more leukocytes in the area have been previously reported [1, 3, 30]. The present results show that the aggregating response depends on the leukocyte subpopulation studied.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…17,31,32 In addition, HD membrane materials may activate neutrophils 33 and platelets. 34 The abrupt change of hemodynamic and metabolic balance caused by dialysis may also add to the development of OS. Further research should be planned in order to accurately measure OS in time intervals between and during dialysis as well as following various time courses and dialysis therapy schemes.…”
Section: Discussionmentioning
confidence: 99%
“…16 In previous studies we have demonstrated leukocyte activation in uremic patients. 2,17 In the present study, we have explored the relationship between expression of CD11b, leukocyte adhesion and the phosphorylation status of tyrosine, serine and threonine residues of CD11b in leukocytes from uremic patients at baseline and throughout haemodialysis with a cellulose membrane.…”
mentioning
confidence: 99%